Differentiated Thyroid Cancer: Changes In The Pulmonary Function Test Post First Radioactive Iodine Treatment - Muhamad, Dr. Nor Qistin (2019)
A thyroid disease could be benign or malignant. Management of thyroid disease has been well established and documented following the American Thyroid Association Guidelines. Radioactive Iodine (RAI) or Iodine-131 (131I) is used to treat differentiated thyroid cancer and benign hyperthyroidism. Radiation pneumonitis and lung fibrosis are lungs complication beside other complication after the exposure of Iodine-131. Differentiated Thyroid Cancer (DTC) patients have longer survival rate as compared to other solid tumour even if the patients had distant metastasis at first diagnosis. Thus, having good lung function is essential for the survival and quality of life. Recent study showed that lung function of some patients with lung metastasis has been found severely impaired during follow-ups.